Gay Berlin : birthplace of a modern identity - Beachy, Robert, 1965- 05.01.1965- (A Borzoi book, 2014)
"A detailed historical look at the surprising ways in which the uninhibited urban sexuality, sexual experimentation and medical advances of pre-Weimar Berlin created and molded our modern understanding of sexual orientation and gay identity. Long known for the friendly company of its "warm brothers" (German slang for men who love other men), Berlin, even before the turn of the twentieth-century, was a place where educators, activists, and medical professionals could explore and begin to educate both themselves and Europe about new and emerging sexual identities. From Karl Heinrich Ulrichs, a German activist described by some as the world's first openly gay man, to the world of Berlin's vast homosexual subcultures-tolerated and monitored by the police commissioner through the "Department of Homosexuals and Blackmailers"-to a major sex scandal that enraptured the daily newspapers and shook the court of Emperor William II, and on through some of the world's first sex reassignment surgeries, Beachy deftly guides the reader through past events and developments that continue to shape and influence the way we think of sexuality to this day. Gay Berlin is certain to be considered a foundational study"..